HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL TERHADAP DURASI TIDUR DAN STATUS GIZI MAHASISWA S-1 ILMU GIZI - Devi Shofiya Husna; Ikha Deviyanti Puspita (JURNAL RISET GIZI, 2020)
Background: Adolescence is a transition period marked by one of them with physical changes so that they are vulnerable to experiencing nutritional problems. Nutritional problems that often occur in adolescents are multiple nutritional problems, namely poor underweight and overweight. Nutritional status can be influenced by several factors including the intensity of social media usage and sleep duration.Objectives: The purpose of this study was to determine the correlation between intensity of social media usage with sleep duration and nutritional status on nutritional science students in University of Pembangunan Nasional Veteran Jakarta.Method: The research design used was a cross sectional study involving 50 respondents from Nutritional Sciences students of 2017 and 2018 who were selected by stratified random sampling. This study uses the Chi Square test with a significance level of 0.05.Result: The results of bivariate analysis showed that there was a significant correlation between intensity of social media usage with sleep duration (p-value = 0,000), a significant correlation between intensity of social media usage with nutritional status (p-value = 0.015), and a significant correlation between sleep duration with nutritional status (p-value = 0.005).Conclusion: There was correlation between intensity of social media usage with sleep duration and nutritional status on Nutritional Science students in University of Pembangunan Nasional Veteran Jakarta.